2022
DOI: 10.1002/rob.22066
|View full text |Cite
|
Sign up to set email alerts
|

Rapid location technology of odor sources by multi‐UAV

Abstract: A multi-unmanned aerial vehicle (UAV) offers the advantages of flexibility, safety, and efficiency with respect to odor source localization. When the traditional particle swarm optimization (PSO) algorithm is used to locate the odor source, the search efficiency of the UAVs is reduced owing to unplanned search routes, and local extreme points and internal collisions may occur, making it impossible to quickly locate the odor source. In response to these problems, this paper proposes an improved particle swarm o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It has been shown that mammals use spatial-temporal olfactory information to navigate and locate sources . As a result, there is considerable interest in providing similar capabilities to robots and UAVs to enable these sorts of tasks in autonomous and stand-off monitoring systems. To explore the feasibility of using temporal modulated responses for plume tracking, a concentration profile (Figure a) was simulated to represent temporal variations that could be experienced by an organism or an autonomous tracking system maneuvering up a concentration gradient to a source, periodically exiting the plume and returning based on a drop in concentration .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that mammals use spatial-temporal olfactory information to navigate and locate sources . As a result, there is considerable interest in providing similar capabilities to robots and UAVs to enable these sorts of tasks in autonomous and stand-off monitoring systems. To explore the feasibility of using temporal modulated responses for plume tracking, a concentration profile (Figure a) was simulated to represent temporal variations that could be experienced by an organism or an autonomous tracking system maneuvering up a concentration gradient to a source, periodically exiting the plume and returning based on a drop in concentration .…”
Section: Resultsmentioning
confidence: 99%
“…The trajectory planning problems in the plan-based control paradigm, in general, are solved adhering to these steps: path search (Wang et al, 2023), initial trajectory generation and trajectory refinement (Liu et al, 2022), high-level control command generation that can be achieved by several approaches, including differential flatness mapping (Talke et al, 2022), receding horizon planning, and finally low-level control commands generation using a flight controller, for example, PX4, DJI. These flight controllers operate independently irrespective of high-level planners.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The rapid development of UAV technology has provided an excellent platform, which has led to the 3D spatial OSL problem based on the UAV platform receiving the attention of most researchers (Jing et al, 2021). Preliminary research results have been achieved (Neumann et al, 2013;Pobkrut et al, 2016;Villa et al, 2016;Luo et al, 2018;Gunawardena et al, 2021;Liu et al, 2022). However, compared with OSL in two dimensions, these results are still far from adequate and need further exploration.…”
Section: From D To Dmentioning
confidence: 99%